PENGARUH INTERAKSI TQM, SISTEM PENGHARGAAN, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL PADA BBWS SUMATERA VIII PALEMBANG - Azizah, Nur; Tripermata, Lukita; Meiriasari, Vhika (STIE Mahardhika, 2024)
Success in a company is closely related to the human resources (HR) within it. Therefore, the organization must support all elements of its human resources well, in order to maximize performance by observing total quality management, reward systems, and environmental uncertainty on managerial performance at the Palembang VIII Sumatra River Region Center. This research uses primary data with a Likert scale. The research method used is a quantitative approach with a questionnaire as a data collection method. This research uses a purposive sampling technique. The sample in this study was at the managerial level, namely commitment making officials (PPK) and financial managers, totaling 54 people. Meanwhile, the data analysis method uses SEM-PLS ver. 04.The results of this research indicate that total quality management has a significant positive effect on managerial performance. Furthermore, the reward system has a significant positive effect on managerial performance. Finally, environmental uncertainty has a significant positive effect on managerial performance.